2016
DOI: 10.1371/journal.pbio.1002571
|View full text |Cite
|
Sign up to set email alerts
|

snRNA 3′ End Processing by a CPSF73-Containing Complex Essential for Development in Arabidopsis

Abstract: Uridine-rich small nuclear RNAs (snRNAs) are the basal components of the spliceosome and play essential roles in splicing. The biogenesis of the majority of snRNAs involves 3′ end endonucleolytic cleavage of the nascent transcript from the elongating DNA-dependent RNA ploymerase II. However, the protein factors responsible for this process remain elusive in plants. Here, we show that DEFECTIVE in snRNA PROCESSING 1 (DSP1) is an essential protein for snRNA 3′ end maturation in Arabidopsis. A hypomorphic dsp1-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 54 publications
2
48
0
Order By: Relevance
“…Neither dsp1-1 nor dsp4-1 altered the abundance of mature snRNAs (Fig. 4, B and E), consistent with observations in other dsp mutants and in int metazoan mutants (Tao et al, 2009;Liu et al, 2016). Interestingly, both RT-qPCR and northern-blot analyses showed that the levels of mature snRNAs were reduced in dsp1-1 dsp4-1 compared with the wild type and single mutants (Fig.…”
Section: Dsp1 and Dsp4 Synergistically Affect The Accumulation Of Presupporting
confidence: 88%
See 4 more Smart Citations
“…Neither dsp1-1 nor dsp4-1 altered the abundance of mature snRNAs (Fig. 4, B and E), consistent with observations in other dsp mutants and in int metazoan mutants (Tao et al, 2009;Liu et al, 2016). Interestingly, both RT-qPCR and northern-blot analyses showed that the levels of mature snRNAs were reduced in dsp1-1 dsp4-1 compared with the wild type and single mutants (Fig.…”
Section: Dsp1 and Dsp4 Synergistically Affect The Accumulation Of Presupporting
confidence: 88%
“…The ratio of heterozygous versus wild-type plants in the progeny of DSP4/dsp4-1 crosses was 1.24:1, which is less than the 2:1 ratio expected by Mendelian inheritance (Supplemental Table S1). This result suggested that, like DSP1 (Liu et al, 2016), DSP4 may also reduce gametophyte transmission. To determine whether dsp4-1 affects female or male gametophyte transmission, we performed reciprocal crosses between DSP4/ dsp4-1 and the wild type.…”
Section: The Dsp4-1 Mutation Impairs Development and Male Gametophytementioning
confidence: 94%
See 3 more Smart Citations